The Analysis of Reading Comprehension Question Levels in English Textbook for Vocational High School Based on Revised Bloom's Taxonomy - Intan Kumala Sari; Sahuddin; Yuni Budi Lestari (Program Studi Pendidikan Bahasa Inggris, 2023)
Reading question is one of the tools that can improve students’ critical thinking. In teaching and learning process, providing questions at the HOTS level really helps students to improve their comprehension. This study aims to analyze the category of cognitive levels in reading questions based on Revised Bloom’s Taxonomy in English textbook “forward an English” for 10th Grade Students of Vocational High School. It used descriptive qualitative research. The data of this study was all of reading comprehension questions found in the textbook. Based on the results, researcher found 202 reading comprehension questions in total which is divided into LOTS level that consist of 133 questions or 65.8% and HOTS level that consist of 69 questions or 34.2%. The most dominant category represented in the English textbook was “remembering” level with 78 questions or 38.6% and the lowest category was “applying” level with 4 questions or 2.0 %. In conclusion, the most of the reading comprehension questions in the English textbook “Forward an English” were at the low level of the cognitive domain. Therefore, the teacher must develop more questions in HOTS level so that the students’ need are in accordance with the demands of 2013 curriculum